Fixed and essential oil composition of Hypericum venustum, Hypericum scabrum and Hypericum spectabile species - Gedik, Osman (Progress in Nutrition, 2022)
This study attempts to determine the oil compositions of H. venustum Fenzl, H. scabrum L., and endemic H. spectabile Jaub. & Spach species by extracting the essential oil from the samples taken during the flowering period, the essential oil and fixed oils from the fruits taken during the seed period. Plant samples of these species were collected from the natural flora of Kahramanmaras in 2020. The essential oil content of these species was identified as 0.20- 0.27% in the flowering period, and 1.25%-2.62% in the fruits taken during the seed period. Essential oils were extracted in Neo-clevenger apparatus, fixed oils were extracted in Soxhlet device. The components of the extracted oils were analyzed by GC/MS in the West Mediterranean Agricultural Research Institute (BATEM) laboratory. The essential oil samples collected during the flowering period consisted of 35 components, and the main component was α-pinene. This component (α-pinene) was 15.06% in H. venustum, 73.77% in H. scabrum and 60.21% in H. spectabile. The essential oil obtained from the fruits in the seed period held a total of 13 different components, and the main component was similarly α-pinene. This component (α-pinene) was determined to be 90.55% in H. venustum, 89.96% in H. scabrum and 82.88% in H. spectabile. The fixed oil rate in the fruits taken during the seed period varied between 16.89% and 24.43%. In fruit samples, six of the fixed oil components had a ratio of over 91%. The rate of unsaturated fat (81.30-91.23%) in the fruits of the Hypericum plant was considerably higher than the saturated fat rate (7.74-9.78%). The main fixed oil component was unsaturated fatty acids linolenic and linoleic acid.